السياحة الإلكترونية كآلية لتنشيط الصناعة السياحية؛ التجربة المصرية - مليكاوي, مولود (جامعة الوادي - University of Eloued, 2022)
يهدف هذا البحث إلى التطرق لمفهوم السياحة الإلكترونية كأحد تطبيقات تكنولوجيا المعلومات والاتصالات ودورها في تعزيز الصناعة السياحية لدى الدول وأهميتها بالنسبة للاقتصاد القومي، وكذا أسباب تطورها وزيادة انتشارها خاصة لدى الدول ذات الجاذبية السياحية، وأهم متطلبات نجاحها مع الإشارة للتجربة المصرية في مجال تطبيق السياحة الإلكترونية والتنوع في المنتج السياحي. وقد خلصت الدراسة إلى الأهمية الكبيرة للسياحة الإلكترونية في دعم الاقتصاد القومي وزيادة تنافسية الدولة في المجال السياحي وذلك ضمن أسس ومرتكزات لعل من أهمها التقدم في مجال تكنولوجيا المعلومات والاتصالات وتوافر إطار مؤسسي وتنظيمي وكذا وجود حد أدنى من استعمال التجارة الإلكترونية في المعاملات المختلفة بالإضافة إلى توافر البيئة الثقافية المساندة. This research aims to addressing the electronic tourism concept as one applications of telecommunication and information technology (TIC) in field of tourism industry and its importance relatively of national economy, as well as the causes of its development and increase their prevalence especially in countries with tourist attractions, the main requirements its success with reference to the Egyptian experience in field of application electronic tourism and diversity in tourism product. The study conclude the importance of electronic tourism in support national economy and increase the competitive of country in field of tourism within the foundations such as the progress in telecommunications and information technology (TIC) and the availability of institutional and regulatory framework as well as exist the minimum of use the electronic commerce in different transactions, in addition to the availability of the supportive cultural environment.
The electronic tourism as a mechanism to activate the tourism industry; Egyptian experience
مقال
Keywords: سياحة إلكترونية؛ تكنولوجيا المعلومات؛ منتج سياحي؛ التجربة المصرية.